The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/iroh.200310683
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effect of Cyprinid Fishes on Phytoplankton and Zooplankton Communities in a Shallow Water Protection Reservoir

Abstract: The effects of fish kill and different fish stocks on the phytoplankton and zooplankton dynamics were studied in a shallow hypertrophic reservoir system. When fish stock was below 100 kg ha -1 , nutrient availability was not the main limiting factor for growth of phytoplankton. Consequently top-down forces controlled phytoplankton. In the years with high fish stock (>100 kg ha -1 ) the bottom-up forces dominated as nutrient availability was the main limiting factor for growth of phytoplankton. We can conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These studies argued that the omnivore roach benefits from its plastic feeding and foraging strategy against the visual predator perch (P. fluviatilis L. 1758), mainly in younger (1þ, 2þ) age groups. In case of Lake Hídvégi, the mechanism might be similar, as young gibel carp feeds mostly on zooplankton (Specziár et al, 1997;Paulovits et al, 1998), which could be the limiting factor under cyanobacteria-dominated hypertrophic conditions (Jeppesen et al, 1998;Mátyás et al, 2004). It should be mentioned, however, that roach can switch to benthivorous strategy earlier (Lappalainen et al, 1975).…”
Section: Eutrophication As a Potential Invasion Limiting Factormentioning
confidence: 99%
“…These studies argued that the omnivore roach benefits from its plastic feeding and foraging strategy against the visual predator perch (P. fluviatilis L. 1758), mainly in younger (1þ, 2þ) age groups. In case of Lake Hídvégi, the mechanism might be similar, as young gibel carp feeds mostly on zooplankton (Specziár et al, 1997;Paulovits et al, 1998), which could be the limiting factor under cyanobacteria-dominated hypertrophic conditions (Jeppesen et al, 1998;Mátyás et al, 2004). It should be mentioned, however, that roach can switch to benthivorous strategy earlier (Lappalainen et al, 1975).…”
Section: Eutrophication As a Potential Invasion Limiting Factormentioning
confidence: 99%
“…Although not specifically incorporated into our models, all studies suggested that some limiting nutrients increased following the MME-increasing NO 3 - (Nagdali and Gupta 2002), soluble P and NO 3 - (Vanni et al 1990), total and soluble reactive P (Mátyás et al 2004); however, the three studies showed various degrees of an initial fertilization effect, including no initial increase in resource abundance (Fig. 6a), a short-term positive impact on resource abundance (Fig.…”
Section: Confronting Model Predictions With Observational Mme Time Sementioning
confidence: 99%
“…Three studies, all from fish MMEs, presented time-series data that was sufficient to graphically visualize MME dynamics (Vanni et al 1990, Nagdali and Gupta 2002, Mátyás et al 2004. We extracted data from these studies using Image J ver.…”
Section: Confronting Model Predictions With Observational Mme Time Sementioning
confidence: 99%
See 1 more Smart Citation
“…In carp dominated the stocking, but still it was too small proportion accounted for predatory fish. In this way effect "bottom up" was reinforced and it was adjusted to the deterioration of water quality (Mátyás et al 2004). When planning stocking, the operation of bio manipulation were not used to improve water quality (Prejs 1978, Benndorf 1995, Tátrai et al 1998, Dawidowicz et al 2002.…”
Section: Optimal Fishery Managementmentioning
confidence: 99%